Anomalous binding memory in heterogeneous molecular systems - Qin, Shiyi; Lyu, Fangxuan; Quan, Xuebo; Miao, Bing; Huang, Kai (浪淘沙预印本平台, 2026)
Understanding how molecular binding couples with diffusion is fundamental to molecular engineering and biomedical applications. At the mesoscale, this coupling gives rise to a binding memory effect, characterized by power-law decays in temporal binding autocorrelations. This repeated binding-unbinding cycles transforms the static, affinity-limited binding picture into a dynamic landscape. While scaling theory has successfully described simple systems, the nature of this coupling in realistic, heterogeneous environments remains poorly understood. Here, we combine high-throughput simulations, theoretical analysis and numerical modelling to reveal how environmental heterogeneity reshapes binding memory and transport statistics. We show that hopping, a nonlocal jump process, induces strong spatiotemporal correlations across binding sites. This leads to diffusion with non-Gaussian statistics and a spectrum of anomalous scaling behaviors for binding memory. In contrast to the universal scaling observed in homogeneous settings, the complex binding-diffusion interplay in heterogeneous binding landscape renders binding memory a tunable property, opening new avenues for molecular-level engineering of chemical reactions, catalysis, and materials design.